L’exil chilien en France entre mobilités transnationales et échanges - Nicolas Prognon (Amnis)
During the twentieth century, a growing number of exchanges and a variety of transfers took place between France and Chile, they skyrocketed in the seventies due to political and conjunctional reasons. With the election of Salvador Allende at the head of the Chilean republic in September 1970, the country became a center of interest for the French, fascinated by « the Chilean road to socialism ». This political experience gave French left-wing intellectuals food for thought. Moves to Santiago led to ideological transfers and then to the mythification of the popular Unity and of Salvador Allende. In 1973, september 11th, the military coup reversed this trend and brought about an exchange towards France. Thousands of Chileans fled their country to find refuge in France, where the military coup had strong effects/echoes. This transfer of population led to a real denunciation work. In spite of the mitigated return of a segment of this population, some unfailing bonds have been tied, evidence of cultural and political transnationalism.